2022
DOI: 10.1155/2022/6403090
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Optimization of Extracellular Lipase from a Novel Strain Kocuria flava Y4

Abstract: The exogenous lipolytic activities of Kocuria sp. have been recognized earlier but the genus further contains many more unexplored strains. In this study, the extracellular lipase activity of Kocuria flava Y4 (GenBank accession no. MT773277), isolated from Dioscorea villosa during our previous study, was regulated by different physicochemical parameters, such as pH, temperature, shaking speed, and incubation time. For efficient immobilization of the extracellular lipase, 4% sodium alginate, 50 mL of 25 nM CaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This indicates that Pseudomonas aeruginosa can produce lipase at 35 o C. It appears that the lipase activity slightly increased at 45 o C, possibly due to environmental factors (Figure 2). Similarly, lipase production by Pseudomonas sp., Penicillium fellutanum, Kocuria flava Y4, and Providencia stuartii was stimulated at 35 o C. [26][27][28][29] Lipase from Staphylococcus sp., Bacillus cereus, and Geobacillus stearothermophilus, on the other hand, were maximally obtained at 37 o C, 30 45 o C, 31 and 60 o C, 32 respectively. This shows that the physical properties of the cell membrane, energy metabolism, and translational synthesis of proteins are affected by temperature.…”
Section: Resultsmentioning
confidence: 98%
“…This indicates that Pseudomonas aeruginosa can produce lipase at 35 o C. It appears that the lipase activity slightly increased at 45 o C, possibly due to environmental factors (Figure 2). Similarly, lipase production by Pseudomonas sp., Penicillium fellutanum, Kocuria flava Y4, and Providencia stuartii was stimulated at 35 o C. [26][27][28][29] Lipase from Staphylococcus sp., Bacillus cereus, and Geobacillus stearothermophilus, on the other hand, were maximally obtained at 37 o C, 30 45 o C, 31 and 60 o C, 32 respectively. This shows that the physical properties of the cell membrane, energy metabolism, and translational synthesis of proteins are affected by temperature.…”
Section: Resultsmentioning
confidence: 98%
“…Kocuria (the phylum Actinobacteria) was also found in PET during the fermentation stage 2 . The members of this genus have extracellular lipase activity, extracellular amylase, and laccase activity 20,21 . Kocuria koreensis , previously isolated in fermented seafood, was positive for catalase, esterase, esterase lipase, β ‐glucosidase, ans so on, 22 and we isolated it from LBT during the pile fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Correlation analysis showed that Staphylococcus , Kocuria , Blastobotry , and Trichomonascus were positively correlated with α ‐linolenic acid. Kocuria has extracellular lipase activity, 21 and Trichomonascus can secrete lipase 31 . However, the mechanism by which these microorganisms promote α ‐linolenic acid production needs to be studied further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipase and protease produced by microbial are more valuable compared to those derived from plants or animals due to their variety of catalytic activities available, high yield production, simplicity of genetic manipulation, absence of seasonal fluctuations, regular supply, more stability, and more safety and convenience, and the growth rate of microorganisms is very high in economical media. [23,24]. 1, and 37.03%, respectively.…”
Section: Production and Purification Of Enzymes Extracellularmentioning
confidence: 94%